Asymptotic Structure of Graphs with the Minimum Number of Triangles. (4th May 2016) - PIKHURKO, OLEG; RAZBOROV, ALEXANDER
Abstract : We consider the problem of minimizing the number of triangles in a graph of given order and size, and describe the asymptotic structure of extremal graphs. This is achieved by characterizing the set of flag algebra homomorphisms that minimize the triangle density.